The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1021/ja208675p
|View full text |Cite
|
Sign up to set email alerts
|

N2 Functionalization at Iron Metallaboratranes

Abstract: The reactivity of the anionic dinitrogen complex [(TPB)Fe(N2)]− (2, TPB = tris-[2-(diisopropylphosphino)phenyl]borane) towards silicon electrophiles has been examined. Compound 2 reacts with trimethylsilyl chloride (TMSCl) to yield the silyldiazenido complex (TPB)Fe(NNSiMe3) (3), which is reduced by Na/Hg in THF to yield the corresponding sodium-bound anion [(TPB)Fe(NNSiMe3)]Na(THF) (4). The use of 1,2-bis(chlorodimethylsilyl)ethane in the presence of excess Na/Hg results in the disilylation of the bound N2 mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
170
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 187 publications
(178 citation statements)
references
References 41 publications
8
170
0
Order By: Relevance
“…Though there are no examples of iron species that are coordinated by the parent diazenido ligand (Fe-N 2 H), complexes of the type Fe(η 1 -N 2 R) can be accessed via alkylation or silylation of a precursor dinitrogen complex Fe(η 1 -N 2 R), 9g,33 or by deprotonation of a hydrazine species Fe(η 1 -N 2 H 3 Ph) (with concomitant H 2 release). 6d It is anticipated that hydrazido oxidation may be a viable synthetic route to diazenido species, by analogy to hydrazine oxidation to give diazene species.…”
Section: Resultsmentioning
confidence: 99%
“…Though there are no examples of iron species that are coordinated by the parent diazenido ligand (Fe-N 2 H), complexes of the type Fe(η 1 -N 2 R) can be accessed via alkylation or silylation of a precursor dinitrogen complex Fe(η 1 -N 2 R), 9g,33 or by deprotonation of a hydrazine species Fe(η 1 -N 2 H 3 Ph) (with concomitant H 2 release). 6d It is anticipated that hydrazido oxidation may be a viable synthetic route to diazenido species, by analogy to hydrazine oxidation to give diazene species.…”
Section: Resultsmentioning
confidence: 99%
“…17). 61,157,191,192,41,44,165 Peters has shown that phosphine ligands provide excellent platforms for functionalization of N 2 on iron, 60,193,194 and enable characterization of potential N 2 reduction intermediates Fe-N x H y , 98,99,165,194196 including systems that feature a coordinated hydride. 40,42,43 Ammonia production by tripodal trisphosphine ligands with an axial donor (Si, C, or B) increases in the order Si < C < B.…”
Section: Fe-nxhy Complexes With Sulfur Ligandsmentioning
confidence: 99%
“…[77] An important feature of the (TP iPr B)Fe system {TP iPr B = tris[2-(diisopropylphosphanyl)-phenyl]borane}, is the presence of a flexible Fe-B interaction. [78,79] The four-coordinate iron complex [37] The catalytic activity is slightly lower than the activities of Mo catalysts (8.5 equiv. NH 3 per Fe equiv.…”
Section: Ch]mentioning
confidence: 99%